The defonologization of the phoneme /λ/ in university students of Arequipa - Cuba Raime, Claret (2004)
The present study aims to analyze the defonologization of /λ/ in Arequipa -Andean region- which is geographically and linguistically considered as lleísta (that is, it maintains the distinction between /λ/ and /y/).